(untitled) (Semiárida, 2018)
Studying the biochemical and physiological responses of plants with different capacities to deal with water stress is a valid approach to identify indicators of drought tolerance. Relative water content (RWC), osmotic potential (Ѱo), greenness index, proline accumulation and contents of chlorophyll and carotenoids were analyzed in four wheat (Triticum aestivum L.) cultivars, under conditions of water supply suppression during a period of 15 days from the start of stem elongation, to determine differences in their response to drought. Irrigation withdrawal caused a significant reduction in RWC and Ѱo. Differences in proline accumulation were observed among assayed genotypes. Hydric stress induced a large proline accumulation in ACA 315 and Baguette Premium 11 stable cultivars. Watering deprivation did not cause significant effects on the content of pigments. The higher proline accumulation of ACA 315 and Baguette Premium 11 may be a relevant fact to explain the stability of such cultivars. It is concluded that concentration of accumulated proline could be used as a biochemical indicator of drought tolerance in wheat at the start of stem elongation. DOI: http://dx.doi.org/10.19137/semiarida.2017(02).5157